Pharmacological Composition of Thymus Serpyllum and Its Components - Aitbekov, R.; Zhamanbayeva, G.; Aralbaeva, A.; Zhunussova, G.; Zhumina, A.; Dodonova, A.; Zhusupova, A.; Umbetyarova, L.; Yeszhanov, B.; Zhaparkulova, N.; Murzakhmetova, M.; Ydyrys, A. (ES Food Agrofor., 2024)
Thymus serpyllum L., a member of the Lamiaceae family, thrives across Eurasia, excluding the tropics, as well as in North Africa, on the Canary Islands, and in North–West Greenland. Its aboveground parts are widely used in ethnomedicine, mainly for treating diseases related to the respiratory and gastrointestinal systems. Recently, its essential oils have become increasingly popular as an important product of plant origin. The composition of these oils depends on the geographical region, the stage of plant development, the harvest season, habitat, and climatic conditions. Thymus serpyllum essential oil has recently been used in modern medicine due to its pharmacological properties, such as antioxidant, antimicrobial, and anti-carcinogenic activity. The antioxidant and antimicrobial properties of Thymus serpyllum essential oil are attributed to its components' synergistic and cumulative action. Further research is needed to explore its potential anticancer and cytotoxic effects and enhance its cytotoxic properties for the development of corresponding medicinal preparations. Thymus serpyllum essential oil, derived from the plant traditionally used in medicine, represents a significant natural resource for the pharmaceutical industry due to its pharmacological properties. Additionally, it can serve as a source of natural antioxidants, food additives, or components for functional food products in the food industry.
Keywords: Thymus serpyllum; Flavonoids; Thyme; Antioxidant; Anticancer; Antimicrobial